Pesan Dakwah dalam Buku “Menyembah Tuhan Yang Salah” - Imaduddin, Muhamad Khalid (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2022)
This paper thoroughly describes the forms of da'wah messages contained in the book Worshiping The Wrong God by Ahmad Rifa'i Rif'an in terms of the category of da'wah messages and message equalization techniques. The research method used in this research is a descriptive method, which is a series of procedures and also stages in carrying out research activities with the aim of solving problems with Ahmad Rifa'i Rif'an's book entitled